The Essence of Neural Networks : Essence of computing
The Essence of Neural Networks is designed to be a first course on neural networks for undergraduate students, with the mathematics contained to a minimum. The book\\\\\\\\\\\\\\\'s main aim is to cover the basic concepts, with the key neural network models explored sufficiently deeply to allow a competent programmer to implement the networks in a language of their choice.